The Limits of Cost/Benefit Analysis When Disasters Loom. (May 2016) - Rose‐Ackerman, Susan
Abstract: Advances in estimating the costs and benefits of climate change policies are a welcome development, but a full‐scale cost/benefit analysis that seeks to reduce complex value trade‐offs to a single metric of net benefit maximization hides many important public policy issues, especially for disasters and catastrophes that are large, discontinuous, irreversible and uncertain. States should obtain public input on such policies. These policies involve value trade‐offs that can be informed by technocratic estimates of costs, benefits and risk. However, such analyses cannot, in principle, be reduced to a single recommendation that 'maximizes net benefits'. Politicians must make value trade‐offs informed both by technocrats and by public input. Abstract : Advances in estimating the costs and benefits of climate change policies are a welcome development, but a full‐scale cost/benefit analysis that seeks to reduce complex value tradeoffs to a single metric of net benefit maximization hides many important public policy issues, especially for disasters and catastrophes that are large, discontinuous, irreversible, and uncertain.